PELATIHAN PEMANFAATAN DAN PENGOLAHANSINGKONGMENJADI MAKANAN RINGAN TELA RASA - Muntoha Muntoha (Asian Journal of Innovation and Entrepreneurship, 2015)
Cassava is a staple food of Indonesian society besides rice and sago. It tastes goodand very filling makes it a staple food was good. The government also continues todisseminate to reduce the consumption of rice and replace it with cassava, sago, corn, orpotatoes. Cassava itself is very easy to grow and maintain. As happened at Dusun Bandungand Dusun Songbanyu 1, Kecamatan Giri Subo, Gunung Kidul, Daerah IstimewaYogyakarta. There are a lot of cassava in the two villages. This prompted author tosimultaneously training initiative provides insight processed cassava innovative and creativeto citizens of those two villages. In addition to its abundant, cassava itself is very useful forthe human body. Inovation that are made by author istasteful cassava snacks. This uniquepreparations can be commodity trades and new entrepreneurs for citizens of those twohamlets.